2005
DOI: 10.1614/wt-04-280r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa) Cultivar Tolerance to Clomazone in Water-Seeded Production1

Abstract: A field study was conducted in 2002 and 2003 to evaluate tolerance of eight rice cultivars to clomazone at 896 g ai/ha impregnated onto urea fertilizer. Rice foliar bleaching was 16 to 20% at 14 d after rice rooting (DAR) for long-grain cultivars ‘Ahrent’, ‘Cheniere’, ‘Cocodrie’, ‘Cypress’, ‘Francis’, and ‘Wells’ and 23 and 30% for medium-grain ‘Bengal’ and short-grain ‘Pirogue’, respectively, when clomazone was impregnated onto urea. Clomazone reduced the number of tillers/ m2 21 DAR for all cultivars. Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The phytotoxicity symptoms of clomazone applied PRE decreased with time and no injury was found on plants at harvest, similarly to the results reported in other studies under flood irrigation (Webster et al, 1999;Scherder et al, 2004;Zhang et al, 2004Zhang et al, , 2005Mudge et al, 2005a) and in upland rice (Esqueda, 2000). However, some reports indicate that at high rates (> 0.8 kg ha -1 ) rice yield can be reduced (Bollich et al, 2000;Mudge et al, 2005a).…”
Section: Rice Tolerancesupporting
confidence: 87%
See 2 more Smart Citations
“…The phytotoxicity symptoms of clomazone applied PRE decreased with time and no injury was found on plants at harvest, similarly to the results reported in other studies under flood irrigation (Webster et al, 1999;Scherder et al, 2004;Zhang et al, 2004Zhang et al, , 2005Mudge et al, 2005a) and in upland rice (Esqueda, 2000). However, some reports indicate that at high rates (> 0.8 kg ha -1 ) rice yield can be reduced (Bollich et al, 2000;Mudge et al, 2005a).…”
Section: Rice Tolerancesupporting
confidence: 87%
“…However, some reports indicate that at high rates (> 0.8 kg ha -1 ) rice yield can be reduced (Bollich et al, 2000;Mudge et al, 2005a). The moderate visual injury found under sprinkler irrigation agrees with the results of Jordan et al (1998a) who observed lower rice injury when clomazone was applied in dry seeded rice compared to rice seeded after flooding.…”
Section: Rice Tolerancesupporting
confidence: 86%
See 1 more Smart Citation
“…Three cabbage cultivars that exhibited higher levels of chlorosis, including the important hybrid cultivar, Bravo, also had yields reduced by 1.0 lb/acre clomazone in one of the two years of the study. Natural variation in clomazone tolerance among cultivars or genotypes within crop species has also been reported for bean [Phaseolus vulgaris (Sikkema et al, 2006)], corn [Zea mays (Keifer., 1989)], cucumber [Cucumis sativus (Al-Khatib et al, 1995;Staub et al, 1991)], pumpkin [Cucurbita maxima, C. moschata, C. pepo (Harrison and Keinath, 2003)], rice [Oryza sativa (Mudge et al, 2005;Scherder et al, 2004;Zhang et al, 2004)], sweetpotato [Ipomoea batatas (Harrison and Jackson, 2011)], and watermelon [Citrullus lanatus ]. The objective of this study was to evaluate the clomazone tolerance of broccoli cultivars in comparison with cabbage cultivars using greenhouse and field experiments to assess the potential for safely using clomazone for weed management in broccoli.…”
mentioning
confidence: 99%
“…), C. pepo L.; Harrison and Keinath 2003], and rice (Oryza sativa L.; Mudge et al 2005;Scherder et al 2004;Zhang et al 2004).…”
mentioning
confidence: 99%